BODY MASS INDEX AND COMPLIANCE IN PATIENTS WITH CORONARY HEART DISEASE COMORBID WITH DIABETES MELLITUS - J.M, Sanakulov; N.P, Yuldashov; S.SH, Kholikulov; Kh.A, Yuldashova; SH.V, Pirmanov (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: to evaluate the relationship between body mass index and compliance in patients with coronary artery disease comorbid with diabetes mellitus. Material and methods: 148 patients with stable angina pectoris (hereinafter referred to as: stable angina - SA) and type 2 diabetes mellitus (DM), i.e. with IHD+DM. Median age = 60.9±8.5 years. According to the blood glucose level, 3 groups were divided: group 1 – 74 patients whose blood glucose level was ≤ 10.0 mmol/l; Group 2 – 43 patients whose blood glucose level was = 10.1-15.0 mmol/l; Group 3 – 31 patients whose blood glucose levels were ≥ 15.1 mmol/l. Of the entire sample of patients, in 99 (66.9%) cases the body mass index was calculated - BMI, kg/m2 (n=99). The median BMI was 29.0±3.6 kg/m2. Compliance was assessed using the Morisky-Green questionnaire. Results: In patients with coronary artery disease + diabetes, an increase in blood glucose levels ≥ 15.1 mmol/l was associated with a trend towards obesity, which was confirmed by an increase in both the number of patients with obesity and the increase in the degree of obesity in them (p<0.05). In patients with high blood glucose levels, in terms of calculating BMI, there was a more pronounced tendency to obesity and low adherence to drug therapy, while, according to CAG data, the frequency of lesions of the circumflex artery was more than 4.5 times more prevalent, in comparison with lesions of the LAD and RCA. Conclusion: Given the increased risk of diabetes complications in obese patients, clinicians must understand how to treat obesity in patients with diabetes, including adherence to drug therapy, as well as prevention of its complications